2012
DOI: 10.1002/acr.21580
|View full text |Cite
|
Sign up to set email alerts
|

Hip fractures in the United States: 2008 nationwide emergency department sample

Abstract: Objective. To evaluate the recent epidemiology of hip fractures in the US. Methods. We identified hip fracture cases from the 2008 Nationwide Emergency Department Sample, which contains more than 28 million emergency department (ED) records. Results. In 2008, approximately 341,000 (95% confidence interval 323,000 -358,000) patients visited EDs with hip fractures. Of those, 90% were age >60 years. Between ages 60 -85 years, the risk of fracture doubled for every 5-to 6-year increase in age. However, the hip fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 42 publications
6
59
1
1
Order By: Relevance
“…The occurrence of falls followed by proximal femoral fracture occurred predominantly in women (67.4%), corroborating national [25][26][27] and international [5,28] studies. Research conducted in 131 public hospitals in Spain that included 56,500 patients ≥ 60 years, hospitalized for proximal femoral fractures, during the period 2002-2005, showed that 78.5% of the fractures occurred in women [5], rates higher than those found in this study (67.4%).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The occurrence of falls followed by proximal femoral fracture occurred predominantly in women (67.4%), corroborating national [25][26][27] and international [5,28] studies. Research conducted in 131 public hospitals in Spain that included 56,500 patients ≥ 60 years, hospitalized for proximal femoral fractures, during the period 2002-2005, showed that 78.5% of the fractures occurred in women [5], rates higher than those found in this study (67.4%).…”
Section: Discussionsupporting
confidence: 59%
“…There was a predominance of elderly aged ≥ 80 years (46.1%), figures approaching that of the Americans, which revealed that the peak of proximal femoral fractures was in the age range of 85 years. It was also found that, between the ages of 60-85 years, the risk of fracture doubled for each 5-6 years of life [28]. It is emphasized that it is in the age group ≥ 80 years in which there also exists a greater chance of the elderly dying [4], indicating the need to work even harder to prevent fractures and on the recovery of functional independence in this group of patients.…”
Section: Discussionmentioning
confidence: 90%
“…The necessity for a comprehensive preventive policy and planning for future treatment increases the importance of gathering data on the incidence and trends of hip fractures (1,3,6). Regional, sample-sized, and institutional studies have tried to identify frequency, demographic structure, and fracture site, aiming to contribute to preventive policies and treatment planning (1,(4)(5)(6)(7)(8)(9)(10)(11)13,14,16). However, in explaining their own limitations, all of these studies emphasize the need for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, estimates of fracture risk are increasingly important for defining treatment thresholds; treatment of these fractures should, of necessity, begin with prevention, and that underlines the importance of gathering meaningful and accurate data (1-3). Many national and institutional studies have been published, and these studies have assessed the epidemiology and frequency of these fractures, which have a considerable socioeconomic burden worldwide (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…3 The risk of hip fracture dramatically increases after age 65 years in women. 4 Hip fracture often leads to disability 5 and premature death. 6 Ongoing pain and limited physical mobility can severely compromise quality of life.…”
Section: Introductionmentioning
confidence: 99%